Measuring students’ perception of writing web logs in ESL classroom employing the technology acceptance model / Mah Boon Yih, Er Ann Nah - Mah, Boon Yih; Er, Ann Nah (2009)
Web log is an exceptionally valuable tool for the teaching of second language writing, particularly in written communication skills (Johnson, 2004; Wu, 2005). More and more foreign educators have applied this easy-to-use technology to classroom instruction and language learning (Campbell, 2003a; Johnson, 2004). However, what has remained predominantly unknown is Malaysian students’ reaction to writing web logs in English as a Second Language (ESL) classroom. Therefore, the study aims to investigate the perception of writing web logs among the Universiti Teknologi MARA (UiTM) HM115 diploma students who were taking BEL311 English course in their third semester based on the three Technology Acceptance Model (TAM) variables. Specifically, the study sought to identify whether the two TAM determinants-Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) affect the students’ behavioural intention (Bl) to use web logs for specific writing task. This study employed the Davis' TAM (1989) and its questionnaire-based measurement instrument and three hypotheses were formulated based on the objectives of the study. The pilot test’s result had confirmed the reliability of the modified TAM-based questionnaire. The findings showed that students accept writing web logs as classroom activity since they perceived online journals to be more useful rather than easy to use. Additionally, the findings revealed that TAM can be used to diagnose and interpret the attitude of new technology users and most importantly, PEOU, PU, and Bl were positively and highly correlated at a significant level. This result proved that the three proposed hypotheses in the study have failed to be rejected.